Exploring Factors Affecting Students' Mathematics Academic Competency Test Achievement: A Case Study AT SMA Islam Assafiiyah Bekasi - Komarudin Komarudin; Fitriana Ratih Ariningrum; Muhammad Ali Sya’ban; Eki Khaerul Fikri; Laila Syahida; Huri Suhendri (Prima: Jurnal Pendidikan Matematika, 2026)
Abstract The Mathematics Academic Competency Test is designed to assess students' mastery of conceptual understanding, mathematical reasoning, problem-solving, and higher-order thinking skills (HOTS). However, previous studies have mainly focused on assessment development and instructional effectiveness, with limited attention to the factors influencing students' TKA achievement from a qualitative perspective. This study aimed to explore the factors influencing students' Mathematics Academic Competency Test achievement at SMA Islam Assafiiyah Bekasi. A qualitative case study was conducted involving the school principal, vice principal for curriculum affairs, mathematics teachers, and Grade XII students. Data were collected through classroom observations, semi-structured interviews, document analysis, and TKA documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. Trustworthiness was established through triangulation, member checking, dependability, and confirmability. The findings revealed that students' TKA achievement was influenced by internal factors, including limited conceptual understanding, low learning motivation, inadequate problem-solving skills, and weak learning independence, as well as external factors, including insufficient HOTS-oriented instruction, limited TKA-based practice, and suboptimal use of learning resources. These findings highlight the importance of strengthening conceptual learning, HOTS-oriented instruction, and authentic assessment to improve students' readiness for competency-based mathematics assessment. Keywords: academic competency test, mathematics learning, higher-order thinking skills   Abstrak Tes Kompetensi Akademik (TKA) Matematika dirancang untuk mengukur penguasaan peserta didik terhadap pemahaman konsep, penalaran matematis, kemampuan pemecahan masalah, dan kemampuan berpikir tingkat tinggi (Higher-Order Thinking Skills/HOTS). Namun, penelitian terdahulu lebih banyak berfokus pada pengembangan instrumen asesmen dan efektivitas pembelajaran, sedangkan kajian mengenai faktor-faktor yang memengaruhi capaian TKA Matematika melalui pendekatan kualitatif masih terbatas. Penelitian ini bertujuan mengeksplorasi faktor-faktor yang memengaruhi capaian TKA Matematika siswa di SMA Islam Assafiiyah Bekasi. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus yang melibatkan kepala sekolah, wakil kepala sekolah bidang kurikulum, guru matematika, dan siswa kelas XII. Data dikumpulkan melalui observasi, wawancara semi-terstruktur, analisis dokumen, dan dokumentasi hasil TKA, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña. Keabsahan data dijaga melalui triangulasi, member checking, dependabilitas, dan konfirmabilitas. Hasil penelitian menunjukkan bahwa capaian TKA dipengaruhi oleh faktor internal, yaitu rendahnya pemahaman konsep, motivasi belajar, kemampuan pemecahan masalah, dan kemandirian belajar, serta faktor eksternal berupa pembelajaran yang belum berorientasi HOTS, terbatasnya latihan berbasis TKA, dan belum optimalnya pemanfaatan sumber belajar. Temuan ini menegaskan pentingnya penguatan pembelajaran konseptual, pembelajaran berorientasi HOTS, dan asesmen autentik untuk meningkatkan kesiapan siswa menghadapi TKA. Kata kunci: tes kemampuan akademik, pembelajaran matematika, berpikir tingkat tinggi